2012
DOI: 10.4236/fns.2012.311209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aggressive Early High-Dose Intravenous Amino Acid Infusion and Early Trophic Enteral Nutrition on Very Low Birth Weight Infants

Abstract: Objective: Very-low-birth-weight (VLBW) preterm infants are at risk of growth delay if they do not receive adequate nutritional support. This study evaluated the effect of aggressive early high-dose amino acid infusion plus early enteral trophic feeding on growth in VLBW infants within the first day of life. Study Design: The effect of a high-dose 3 g amino acid (HAA)/kg/d regimen beginning on the first day of life was compared with that of low-dose amino acid (LAA) supplementation at a dose of 0.5 or 1.0 g/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…4143 Furthermore, it was reported that simultaneous low-dose amino acid infusion and breast milk feeding reduces the time of mechanical ventilation in premature infants with respiratory distress syndrome, possibly by ensuring improved energy support to aid respiratory muscle strength. 44,45 These studies highlight the advantages of optimizing nutritional support in premature neonates through the implementation of dietary additives. More important, these data suggest that adjusting the diet of late preterm infants to resemble the higher calorie, lipid, and protein diet administered to more premature infants may provide better nutritional support for this population to combat respiratory challenges.…”
Section: Discussionmentioning
confidence: 99%
“…4143 Furthermore, it was reported that simultaneous low-dose amino acid infusion and breast milk feeding reduces the time of mechanical ventilation in premature infants with respiratory distress syndrome, possibly by ensuring improved energy support to aid respiratory muscle strength. 44,45 These studies highlight the advantages of optimizing nutritional support in premature neonates through the implementation of dietary additives. More important, these data suggest that adjusting the diet of late preterm infants to resemble the higher calorie, lipid, and protein diet administered to more premature infants may provide better nutritional support for this population to combat respiratory challenges.…”
Section: Discussionmentioning
confidence: 99%